Clinicopathological Features of Stage I–III Colorectal Cancer Recurrence Over 5 Years After Radical Surgery Without Receiving Neoadjuvant Therapy: Evidence From a Large Sample Study - Luo, Dakui; Yang, Yufei; Shan, Zezhi; Liu, Qi; Cai, Sanjun; Li, Qingguo; Li, Xinxiang (Frontiers in Surgery, 2021)
Late recurrence (5 or more years) after radical resection of colorectal cancer (CRC) is rare. This study aims to investigate the features of late recurrence in stage I–III CRC. A total of 9,754 stage I–III patients with CRC who underwent radical surgery without receiving neoadjuvant therapy, at the Fudan University Shanghai Cancer Center (FUSCC), were enrolled in this study. These patients were divided into three groups: early recurrence (3 months−2 years), intermediate recurrence (2–5 years), and late recurrence (over 5 years). The median duration of follow-up was 53.5 ± 30.1 months. A total of 2,341 (24.0%) patients developed recurrence. The late recurrence rate was 11.7%. Patients with a higher risk of late recurrence were more likely to be older, to be at the T4 stage, to have a higher degree of colon cancer, to have a lower frequency of signet ring cell carcinoma, to have fewer poorly differentiated tumors, to be at the early stage of CRC, along with less perineural and vascular invasions. Multivariate logistic regression analysis identified age, differentiation, T stage, N stage, perineural, and vascular invasions as independent factors for late recurrence. Late recurrent CRC has some distinctive characteristics. Although recurrence over 5 years after surgery is infrequent, an enhanced follow-up is still needed for the selected patients after 5 years.